Insights into the conformational dynamics of the E3 ubiquitin ligase CHIP in complex with chaperones and E2 enzymes - Graf, Christian; Stankiewicz, Marta; Nikolay, Rainer; Mayer, Matthias P. (Biochemistry, 2010)
The dimeric E3 ubiquitin ligase CHIP binds with its tetratricopeptide repeat (TPR) domain the C-terminus of molecular chaperones Hsp70 and Hsp90 and with its U-box region E2 ubiquitin-conjugating enzymes. By ubiquitinating chaperone-bound polypeptides, CHIP thus links the chaperone machinery to the proteasomal degradation pathway. The molecular mechanism of how CHIP discriminates between folding and destruction of chaperone substrates is not yet understood. Two recently published crystal structures of mouse and zebrafish CHIP truncation constructs differ substantially, showing either an asymmetric assembly or a symmetric assembly with a highly ordered middle domain. To characterize the conformational properties of the intact full-length protein in solution, we performed amide hydrogen exchange mass spectrometry (HX-MS) with human CHIP. In addition, we monitored conformational changes in CHIP upon binding of Hsp70, Hsp90, and their respective C-terminal EEVD peptides, and in complex with the different E2 ubiquitin-conjugating enzymes UbcH5a and Ubc13. Solution HX-MS data suggest a symmetric dimer assembly with highly flexible parts in the middle domain contrasting both the asymmetric and the symmetric crystal structure. CHIP exhibited an extraordinary flexibility with a largely unprotected N-terminal TPR domain. Formation of a complex with intact Hsp70 and Hsp90 or their respective C-terminal octapeptides induced folding of the TPR domain to a defined, highly stabilized structure with protected amide hydrogens. Interaction of CHIP with two different E2 ubiquitin-conjugating enzymes, UbcH5a and Ubc13, had distinct effects on the conformational dynamics of CHIP, suggesting different roles of the CHIP−E2 interaction in the ubiquitination of substrates and interaction with chaperones.
Gesehen am 08.05.2023